Novel Insights into Lectin Binding Patterns in the Nasopharyngeal Tonsil of Buffaloes (Bubalus bubalis) - Kumar, Pawan (Journal of Buffalo Science, 2025)
Background: The present study investigates the specificity of lectin binding in the nasopharyngeal tonsil of six healthy adult buffaloes (Bubalus bubalis), a species not extensively studied regarding its immune system. Lectins, proteins that bind specifically to carbohydrates, are used to identify and characterize different cell types that may have roles in immune responses. This study explores how lectins bind to various cells within the nasopharyngeal tonsil, shedding light on cellular differentiation, interactions, and the potential functional roles of these cells in mucosal immunity. Method: A total of 21 biotinylated lectins, grouped into five categories based on their carbohydrate specificity (N-acetylglucosamine, N-acetylgalactosamine, galactose, glucose/ mannose, and fucose), were used to probe the nasopharyngeal tonsil tissue. Lectin histochemistry was applied to identify the binding patterns of these lectins to different cell types within the tissue, including epithelial cells, lymphoid cells, and specialized structures such as M-cells and P-cells. The study also involved the detection of vimentin filaments to explore potential immune responses within the tissue. Results: Lectin histochemistry revealed a dynamic epithelial composition of the nasopharyngeal tonsil, consisting of pseudostratified columnar ciliated epithelium and lymphoepithelium, with distinct adaptations in the follicle-associated epithelium (FAE). The FAE exhibited M-cells, which are believed to play a role in antigen processing. Additionally, a new class of cells, termed P-cells, was identified based on their lectin-binding patterns, which share similarities with M-cells but are distinct in their function. Lectins targeting N-acetylglucosamine exhibited varying affinities for M- and P-cells, while lectins recognizing N-acetylgalactosamine selectively bound to cilia and goblet cells. Lectins targeting galactose produced complex staining patterns in mucous glands and lymphoid tissues. Specific binding was also observed in lymphoid cells with lectins recognizing glucose/mannose and fucose groups. Vimentin filaments in lymphocytes and specialized epithelial cells suggest an involvement in immune response mechanisms. Conclusion: This study provides new insights into structural organisation landscape of the buffalo nasopharyngeal tonsil, highlighting the role of lectin-binding patterns in identifying specialized cells and tissues. The M-cells and discovery of P-cells and the detailed lectin-binding profiles may contribute to understanding the cellular dynamics of mucosal immunity. Additionally, the structural details uncovered in this study may serve as a valuable reference for comparative research on mucosal immunity across different species, advancing our understanding of antigen recognition and immune responses at mucosal surfaces.